Ritualized Objects: How We Perceive and Respond to Causally Opaque and Goal Demoted Action - Kapitány, Rohan (Journal of cognition and culture, 2019)
Rituals are able to transform ordinary objects into extraordinary objects. And while rituals typically do not cause physical changes, they may imbue objects with a particular specialness - a simple gold band may become a wedding ring, while an ordinary dessert may become a birthday cake. To treat such objects as if they were ordinary then becomes inappropriate. How does this transformation take place in the minds of observers, and how do we recognize it when we see it? Here, we suggest that two under-examined elements of ritual need deeper consideration within the context of ritual cognition. We propose a fully integrated operational definition in which these two critical ritual elements - causal opacity and goal demotion - are included. In a pre-registered experiment one-hundred and one adults, in a 2 × 2 mixed-within participants design observed actions performed upon profane objects. These actions were either ordinary (causally transparent and goal apparent) or ritualized (causally opaque and goal demoted), and were described as a blessing, a curse, or were not described at all. Contrary to established findings and pre-registered predictions, we found that ritualized actions alone are not enough to influence perceptions of, and attributions towards, objects, and that positive goal information (blessings) are more behaviorally persuasive than negative information. However, we found that participants recalled ritualized action in greater detail and with more specificity than ordinary actions. In effect, we demonstrate that causal opacity and goal information interact to allow us to recognize a ritual as a ritual.